The Influence of Product Innovation, Branch Network, And Informaation Technology Systems on Switching Behavior of Customers from Conventional Banks Syariah Indonesia: A Case Study in Selong District - Muhtar Hafiz; Muslihun Muslihun; Sanurdi Sanurdi (JURNAL PENDIDIKAN IPS, 2025)
This research aims to analyze the influence of product innovation, office networks, and information technology systems on the switching behavior of conventional bank customers who switch to Bank Syariah Indonesia (Case Study in Selong District). The data used is primary data collected through questionnaires/surveys. The population in this study consists of customers of Bank Syariah Indonesia who have previously used the services of conventional banks in the Selong area, with a sample obtained from 100 respondents using purposive sampling technique. In this study, a multiple linear regression analysis method was used. The results of the partial t-test are as follows: 1) Product Innovation has a significant positive effect on the switching behavior of conventional bank customers who switch to Bank Syariah Indonesia, with a sig. value of 0.000>0.05. 2) Office Network does not affect the switching behavior of conventional bank customers who switch to Bank Syariah Indonesia, with a sig. value of 0.559>0.05. 3) Information Technology System has a significant negative effect on the switching behavior of conventional bank customers who switch to Bank Syariah Indonesia, with a sig. value of 0.05=0.05. The F test (sim elevated) shows that product innovation, office network, and information technology system collectively affect the switching behavior of conventional bank customers who switch to Bank Syariah Indonesia in the Selong District. Of the three variables, the one that most dominantly influences switching behavior is the product innovation variable.